2015
DOI: 10.1103/physrevc.92.025806
|View full text |Cite
|
Sign up to set email alerts
|

Systematic study of(α,γ)reactions for stable nickel isotopes

Abstract: A systematic measurement of the (α,γ) reaction for all the stable nickel isotopes has been performed using the γ-summing technique. For two of the isotopes, 60 Ni and 61 Ni, the α-capture cross sections have been experimentally measured for the first time. For 58,62,64 Ni, the current measurement is in excellent agreement with earlier results found in the literature, and additionally extends the energy range of the measured cross sections up to 8.7 MeV. The data provided a tool for testing the cross section pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…A detailed study of the (α, γ) reactions on 74 Ge and 90,92 Zr nuclei [19] has been the newest issue of a major effort to provide a constraint for the choice of input models in a given A range. As for all stable nickel isotopes [66], different best combinations of input parameters for the TALYS 1.6 code were found for each of the investigated isotopes and also at variance with the grounds of the concerned α-particle OMP [67].…”
Section: Recent (α γ) Reaction Data Analysismentioning
confidence: 99%
“…A detailed study of the (α, γ) reactions on 74 Ge and 90,92 Zr nuclei [19] has been the newest issue of a major effort to provide a constraint for the choice of input models in a given A range. As for all stable nickel isotopes [66], different best combinations of input parameters for the TALYS 1.6 code were found for each of the investigated isotopes and also at variance with the grounds of the concerned α-particle OMP [67].…”
Section: Recent (α γ) Reaction Data Analysismentioning
confidence: 99%
“…These studies focused on understanding the sources of uncertainty of the calculated rates [12,13], and evaluating the impact of these uncertainties in network-calculated abundances [14][15][16][17]. On the contrary, equivalent studies on charge-particle reactions are scarce [9,18,19], even though they are known to play a crucial role in the synthesis of light r-process nuclei (from Fe to Ag) through the α (or charge-particle) process (see e.g. [9,20,21]).…”
Section: Introductionmentioning
confidence: 99%
“…Recent high-precision measurements [1][2][3][4][5][6] of α-particle induced reaction data below the Coulomb barrier (B) provide an useful opportunity to investigate the results of a previous optical-model potential (OMP) for α-particles on nuclei within the mass number range 45≤A≤209 [7]. Actually, this potential was established by (1) analysis of α-particle elastic-scattering angular distributions above B [7,8], and (2) Hauser-Feshbach statistical model (SM) assessment of the available (α, γ), (α, n) and (α, p) reaction cross sections for incident energies below B and target nuclei either with A≤120 [9] or heavier [7,10].…”
Section: Introductionmentioning
confidence: 99%
“…However, the abovementioned recent works have pointed out α-particle OMP questions yet open within various mass ranges. Thus, a detailed systematic study of the (α, γ) reactions for all stable nickel isotopes [1], following also recent distinct studies of this reaction on 58 Ni [12] and 62 Ni [13] iso- * Electronic address: vlad.avrigeanu@nipne.ro topes, aimed to provide a constraint for the choice of input models in a given A range. Nevertheless, different best combinations of input parameters for the TALYS 1.6 code [14] were found for each of the investigated isotopes while the combination identified that reproduces simultaneously the experimental data for all Ni isotopes has been at variance with the findings of the distinct studies [12,13] as well as the grounds of the concerned α-particle OMP [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation